2015
DOI: 10.1158/1078-0432.ccr-15-0204
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 and CCL5 Are Novel Therapeutic Targets for Estrogen-Dependent Breast Cancer

Abstract: Purpose: Novel therapeutic targets of estrogen receptor (ER)-positive breast cancers are urgently needed because current antiestrogen therapy causes severe adverse effects, nearly 50% of patients are intrinsically resistant, and the majority of recurrences have maintained ER expression. We investigated the role of estrogen-dependent chemokine expression and subsequent cancer growth in human tissues and experimental breast cancer models.Experimental Design: For in vivo sampling of human chemokines, microdialysi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
150
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(166 citation statements)
references
References 51 publications
13
150
2
1
Order By: Relevance
“…The zebrafish metastasis model allows for such investigation (10,31). By using this model, we showed here that neutrophils increased ER þ breast cancer cell dissemination, which is in agreement with recent published data (7).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The zebrafish metastasis model allows for such investigation (10,31). By using this model, we showed here that neutrophils increased ER þ breast cancer cell dissemination, which is in agreement with recent published data (7).…”
Section: Discussionsupporting
confidence: 92%
“…We have previously shown that E 2 does not affect the number of neutrophils in central tumor tissues and that the numbers of neutrophils in the centers of tumors are very low (10). Our present data suggest that neutrophils are preferentially localized in the invasive margin and that E 2 significantly affects the number of these neutrophils both in immune-competent and immune-deficient mouse models of breast cancer.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In our cohort of pure DCIS, we identified associations between It is not yet conclusively known why some breast carcinomas have higher TILs than others. Polarization toward an immunosuppressive microenvironment due to ER signaling has been suggested as one possibility to explain elevated TILs in ER-negative carcinomas (35). Another is the relationship with genetic aberrations, as in melanoma, because the overall mutational load is much higher in triple-negative than luminal subtype breast carcinomas, with higher potential for neoantigen formation (36).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown increased extracellular in vivo levels of several inflammatory mediators, such as interleukin (IL)-1, IL-8, chemokine (C-C motif) ligand (CCL) 2, CCL5, leptin, and vascular endothelial growth factor (VEGF) in breast cancers of women and an association with sex steroids of these factors in normal human breast tissue. [4][5][6][7][8][9][10][11][12] Mammographic density has been associated with increased risk of breast cancer. 13 In a meta-analysis women with >75% dense breast area have a 4-fold increased risk of developing breast cancer compared to women with <5% dense breast area.…”
Section: Introductionmentioning
confidence: 99%